“The Listening Hand”: Piano Exercises for Contemporary Music - Vickers, Catherine (Musica Docta, 2015)
In the past 12 years, pianist and educationalist Catherine Vickers developed a series of specific piano exercises for contemporary music, which she published under the title Die hörende Hand (“The listening hand”) for Schott publishing, Mainz (two issues, 2007-2008; a third one will be out soon). Tonal music, by virtue of both its chord development in thirds and of its leading-note relationships, prompts pianists to develop special “leaps” of the hand, sometimes even specific muscle mechanisms. However, because contemporary music involves an ever-greater distance from tonality, it is now indispensable to modify, and extend, the internalized ‘leaps’ of the piano tradition to other sound relationships. Thus not only the ear, but especially the hands can ‘dive’ into the various stylistic settings of New Music, as a source of both emotional and physical enrichment. In her article, the author expounds the premises, founding principles and development of these exercises.